INTRUSION DETECTION SYSTEM USING KDD’99 CUP DATASET - Satyendra Vishwakarma & Vivek Sharma (International Journal of Research Science and Management, 2017)
Our effective design of horizontal axis certain angled wind turbines are applicable for side and top of road ways,bridges and top roof.The curved shape six blades are designed to efficiently collect the wind velocity to attain maximum efficiency.The contact distance of the vehicle and blades are indirectly proportional to the power generation.In short distance maximum revolution of blades through wind velocity is obtained to produce maximum power. Our design produces constant power for all the time.The blade connected to the shaft is attached with generator.The device convert mechanical energy into electrical energy by the principle of electromagnetic induction.The direct current stored in a battery and an inverter is used to convert direct current into alternating current for the application of cc TV and lights.